The Influence Of Corporate Resources And Corporate Strategy To Improve Corporate Performance At Indonesian State Owned Enterprises - Harry Gozali; Sucherly .; Yuyus Suryana; Yevis M. Oesman (Jurnal Bisnis Manajemen, 2015)
The existence of Indonesian state-owned enterprises (SOEs) has an important role for the communities’ welfare as it ismandated in the constitution. If traced based on its face value, the profit of Indonesian SOEs looks to continue increasesteadily every year. However, on the other hand there is the biggest challenge, such as how to increase the value ofcompany, which is shown by ROA and ROE that keep on declining. This actually means that it is still possible to get ahigher profit. The objectives of this study are to get assessment regarding to (1) correlations of corporate resources withcorporate strategy, and (2) whether corporate resources and corporate strategy are affecting corporate performance,partially or simultaneously, to the Indonesian SOEs. Units of analyzes were 101 corporations from four different industrysectors and the samples for this research are 50 corporations of Indonesian SOEs. Time horizon is cross-sectional, wherethe study was conducted at a single period of time simultaneously. Data was gathered by questionaires and in-depthinterviews to SOEs directors and functional managers. Data analyzed were both descriptive and quantitative. Hypothesistesting was utilized by PLS model (Partial Least Square) 2.0 version. The finding shown that there are correlationsbetween corporate resources and corporate strategy. Corporate resources and corporate strategy do affect corporateperformance, directly or simultaneously. Moreover, corporate strategy have more influence than corporate resources.Directional strategy and organizational resources are the most dominant dimensions in affecting corporate performanceof Indonesian SOEs. The conclusion from this research is that most of Indonesian SOEs are not capable in formulatingtheir corporate strategy appropriately due to mismatching of their/incompatibility corporate resources.Key words: Corporate Resources, Corporate Strategy, and Corporate Performance.